PENGARUH UKURAN DEWAN DIREKSI, UKURAN KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2011-2014 - PUSPITASARI, BETTI (Jurnal Ilmu Manajemen (JIM), 2016)
This study aimed to determine the effect of board size, board of audit committee and firm size on the performance of companies in the mining sector listed on Indonesia Stock Exchange (BEI) in the period 2011-2014. Samples in this study as many as 28 companies. This study uses secondary data from financial reports and company report published on IDX site. The analysis technique used is multiple linear regression analysis. To test the hypothesis by F test, t test and the coefficient of determination (R ²). F test results showed that there was a simultaneous effect of independent variables on ROA. T test results showed that board size has a significance value of 2.567 at 0.012, the board of audit committee has a significance value of 1.015 at 0.312, and firm size has a significance value of -0.354 at 0.724. Based on data analysis, it can be concluded that the only variable board size has positive effects on ROA. While variable board of audit committee and firm size has no effect on ROA. Keywords: board size, board of audit committee, firm size, ROA.